Peran Prodi Studi Agama-Agama terhadap Religiositas Mahasiswa Studi Agama-Agama - Azmi, Syaiful; Apriliani, Elisa (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2025)
This study analyzes the reality of religiosity of students of the Religious Studies Study Program class of 2020 and the role of the Religious Studies Study Program, Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta in maintaining student religiosity. The main focus of this study is how the quality of religiosity of students of the Religious Studies Study Program and the implementation of the efforts and role of the Religious Studies Study Program in maintaining and improving the religiosity of its students. The research method used in this study is to use a descriptive qualitative method with a sociological approach and religious psychology. The results of this study show that in reality students do not experience a decrease in the quality of their religious beliefs as a Muslim. And the Religious Studies Study Program is able to implement its role and efforts in maintaining and improving student religiosity. The conclusion of this study confirms that a religious education institution which in this study is the Religious Studies Study Program, this is indeed one of the most important factors that has a very large and significant role in maintaining student religiosity.